2006
DOI: 10.1183/09031936.00016106
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of exhaled nitric oxide in pre-term infants with chronic lung disease

Abstract: Animal models suggest that reduced nitric oxide (NO) synthase activity results in lower values of exhaled NO (eNO) present at birth in those individuals who are going to develop chronic lung disease of infancy (CLDI).Online tidal eNO was measured in 39 unsedated pre-term infants with CLDI (mean gestational age (GA) 27.3 weeks) in comparison with 23 healthy pre-term (31.6 weeks) and 127 term infants (39.9 weeks) at 44 weeks post-conceptional age, thus after the main inflammatory response. NO output (NO output (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 32 publications
1
27
3
Order By: Relevance
“…In older infants16 and children17 18 who had had BPD, similar or lower eNO levels compared with controls have been reported. The children, however, were of school age18 or studied between 4 and 25 months17 and the infants examined at 44 weeks PMA,16 when the authors state they felt the main inflammatory process was over.…”
Section: Discussionmentioning
confidence: 56%
“…In older infants16 and children17 18 who had had BPD, similar or lower eNO levels compared with controls have been reported. The children, however, were of school age18 or studied between 4 and 25 months17 and the infants examined at 44 weeks PMA,16 when the authors state they felt the main inflammatory process was over.…”
Section: Discussionmentioning
confidence: 56%
“…Mieskonen et al [137], however, did not find any differences in FE NO between controls and school-age children with CLD. Studies in younger children revealed values to be equal to or higher in patients with CLD compared with controls, although NO output seemed lower in preterm infants with CLD [38,138,165].…”
Section: Chronic Lung Disease Of Prematuritymentioning
confidence: 87%
“…Compared with healthy infants, lower FeNO levels have been found in infants with virus-associated acute, wheezing bronchitis [5] and in infants with upper respiratory symptoms (URS), such as rhinorrhoea [6]. Several preand post-natal factors have been shown to influence the levels of FeNO in infants, such as tobacco smoke exposure [7][8][9], coffee consumption during pregnancy [8], maternal atopic disease [8,10], birth weight [11], gestational age [11,12], sex [8] and infections [13]. However, the influence of risk factors for respiratory morbidity on FeNO in infancy is not clear.…”
mentioning
confidence: 99%